A niche for isotopic ecology. Issue 8 (1st October 2007) - Newsome, Seth D.; Martinez del Rio, Carlos; Bearhop, Stuart; Phillips, Donald L.
Abstract : Fifty years ago, GE Hutchinson defined the ecological niche as a hypervolume in n‐dimensional space with environmental variables as axes. Ecologists have recently developed renewed interest in the concept, and technological advances now allow us to use stable isotope analyses to quantify these niche dimensions. Analogously, we define the isotopic niche as an area (in δ‐space) with isotopic values (δ‐values) as coordinates. To make isotopic measurements comparable to other niche formulations, we propose transforming δ‐space to p‐space, where axes represent relative proportions of isotopically distinct resources incorporated into an animal's tissues. We illustrate the isotopic niche with two examples: the application of historic ecology to conservation biology and ontogenetic niche shifts. Sustaining renewed interest in the niche requires novel methods to measure the variables that define it. Stable isotope analyses are a natural, perhaps crucial, tool in contemporary studies of the ecological niche.